Sistem Pendukung Keputusan Kelompok pemilihan Saham LQ45 dengan menggunakan metode AHP, Promethee dan BORDA - Mauko, Arfan; B, Muslimin; Sugiartawan, Putu (INFOTEKS (Information Technology, Computer and Sciences), 2018)
Investments shares on the Indonesia Stock Exchange is one of the investment with a high rate of return. Stock investment profit greatly influenced by the selection of the right stocks in a portfolio. Analyzing the uncertainty of a stock investor can involve the process of stock selection in group decision which includes investors, investment bankers, analysts, and brokers. Stock selection as a group can produce a stock portfolio with a higher rate of profit than the results of individual decision-making. Implementation of stock selection in group decision support systems (GDSS) used two economic approaches, namely fundamental analysis, and technical analysis. Fundamental analysis uses data financial ratios which have a significant influence on the development of a company's stock. Technical analysis is a stock valuation based on stock movement data time series. This research using AHP, PROMETHEE, and Borda to accommodate the results of shares in group decision making. This research resulted in ranking stocks as a group that can serve as recommendations for investors stock picking.